Identity‐based hate and violence as trauma: Current research, clinical implications, and advocacy in a globally connected world. Issue 2 (27th October 2021) - Allwood, Maureen; Ghafoori, Bita; Salgado, Carolina; Slobodin, Ortal; Kreither, Johanna; Waelde, Lynn C.; Larrondo, Paulina; Ramos, Nadia
Abstract: Hate‐based violence is increasingly recognized as an urgent social justice and human rights issue that is pervasive across geographical and socioeconomic boundaries. There is a growing body of research that demonstrates the traumatic impact of hate‐based violence on the victim's mental and physical health. This review focuses on examining scientific knowledge and prevalence data on identity‐based hate and violence exposure. A framework for conceptualizing hate‐based violence as a traumatic event or series of traumatic events is offered as a means to understand research findings and intervention approaches. The importance of research, advocacy, and human rights training is highlighted in the efforts to address the traumatic impact of identity‐based hate and violence.